CLIMATE CHANGE INDICATION ACROSS FOUR STATES IN NIGERIA: HEAT LOAD INDEX AND MULTIVARIATE ANALYSIS - TOWOLAWI, A. T.; OGUNTOKE, O.; BADA, B. S.; ADEJUWON, J. O.; ABDULSALAMI, B. A.; ADEGBORE, A. K. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2024)
Biometeorologists typify climate change indication on the environment using indices such as the heat load index (HLI) with scales of HLI: ≤ 70.0 for cool, 70.1 to 77 for warm, 77.1 to 86.0 for hot, and ≥86.1 for a very hot environment. The current study adopted HLI computed from temperature, relative humidity, and wind speed data of 32 years (1987-2018) for five locations (Benin, Ondo, Bida, Minna, and Makurdi) and their environs, where rain-fed agriculture does favour yearly agricultural produce. The data were retrieved from the archive of Nigeria Meteorology office, Abuja, analysed with descriptive statistics, and further subjected to multivariate analysis. Average HLI indicated a hot environment for the wet periods except for April, when it was warm at Minna. December to February of dry periods had cool environments in Bida, Niger, Makurdi and their environs. Very strong correlations occurred from April to June, between September and October, and between November and December at a 0.01 significant level from Pearson’s Correlation. The Principal Component Analysis indicated eleven months with 61.00 % variance under Component 1, and four months (January, July, September, and October) among them had eigenvalue less than 0.8, indicating that the entire year except August had climate change indications. The study suggested that the five locations and their environs must understand how to cope with climate change heat load.